Respuesta :

[tex] \frac{2(3 - x)^{ \frac{5}{2} } }{5} - \frac{2(3 - x)^{ \frac{3}{2} } }{3} + C[/tex]is the answer

Step-by-step explanation:-

Given:

[tex]{\int {(x-2)\sqrt{3-x}} \ dx }[/tex]

Differentiate on both sides,

[tex]{\int {(x-2)\sqrt{3-x}} \ dx },u = 3 - x[/tex]

Isolate and substitute back,

[tex]{\int {(x-2)\sqrt{3-x}} \ \times ( - 1) du },u = 3 - x[/tex]

Substitute back,

[tex]{\int ( - ( - u + 3 - 2) \sqrt{u})du }[/tex]

Applying property of integral kf(x)dx = kf(x)dxdx,

[tex] - ∫ ( - u + 3 - 2) \sqrt{u} \: du,u = 3 - x[/tex]

Combining like terms,

[tex]- ∫ ( - u +1) \sqrt{u} \: du,u = 3 - x[/tex]

Now applying distributive property,

[tex]- ∫ (( - u +1) \sqrt{u}) \: du,u = 3 - x[/tex]

[tex] = > - ∫ ( - \sqrt{u} \times u + \sqrt{u} )\: du,u = 3 - x[/tex]

Converting to exponential form,

[tex]- ∫ ( - u^{ \frac{1}{2} } \times u + u^{ \frac{1}{2} } )\: du,u = 3 - x[/tex]

Multiplying the first two monomuals after integral, we get,

[tex]- ∫ ( - u^{ \frac{3}{2} } + u^{ \frac{1}{2} } )\: du,u = 3 - x[/tex]

Now applying the prperty of ∫ f(x) + g(x)dx = ∫ f(x)dx + ∫ g(x)dx,

[tex] - ( - ∫u^{ \frac{3}{2} } \: du + ∫u^{ \frac{1}{2} } \: du),u = 3 - x[/tex]

Now integrate the power rule,

[tex] - ( - \frac{u^{ \frac{5}{2} }}{ \frac{5}{2} } + \frac{u^{ \frac{3}{2} }}{ \frac{3}{2} } ),u = 3 - x[/tex]

Divide the fractions by multiplying its reciprocals,

[tex] - ( - u^{ \frac{5}{2} } \times \frac{2}{5} + u^{ \frac{3}{2} } \times \frac{2}{3}),u = 3 - x[/tex]

Now write as single fractions,

[tex] - ( - \frac{2u^{ \frac{5}{2} } }{5} + \frac{2u^{ \frac{3}{2} } }{3})[/tex]

Removing the parentheses,

[tex] \frac{2u^{ \frac{5}{2} } }{5} - \frac{2u^{ \frac{3}{2} } }{3},u = 3 - x[/tex]

Substitute back,

[tex] \frac{2(3 - x)^{ \frac{5}{2} } }{5} - \frac{2(3 - x)^{ \frac{3}{2} } }{3} [/tex]

Now adding the constant of integration C∈R,

[tex] \frac{2(3 - x)^{ \frac{5}{2} } }{5} - \frac{2(3 - x)^{ \frac{3}{2} } }{3} + C[/tex]

Hence, the answer.